A Study on the Commercial Development of Traditional Art IPs - Zhou, Ruiqi (International Journal of Global Economics and Management, 2024)
Driven by the wave of digitization, traditional art IP, serving as a bridge between cultural heritage and modern commerce, are exhibiting unprecedented vitality and potential. To better tap into their value and achieve sustainable development, this paper proposes that the modern development of traditional art IPs should proceed from multiple aspects, including the application of digital technologies, cross-border integration and innovation, the rise of the creative industries, the extension of the IPs industry chain, specialized operations, policy support and protection, jointly promoting the widespread dissemination and sustainable development of traditional art IPs in modern society.